Pemanfaatkan Bonus Demografi dengan Mewujudkan Generasi Emas Melalui Kecakapan Abad 21 (Current Research in Education: Conference Series Journal, 2022)
The purpose of this article is to study and find solutions to Indonesia's education problems to realize the demographic bonus or golden generation of this 21st century nation. In this article we use a collaborative research method, which is literature-based by collecting data that departs from existing problems. By going through data analysis, we critique, filtering the available data from the source to draw conclusions. From various sources such as journals, the internet and equipped with existing facts. The results of the research and discussion show that in realizing the demographic bonus through good Indonesian education, one of the right ways is by implementing the 4k strategy in teaching and learning activities, namely collaborative, creative and innovative, critical thinking and communication. Of course, this is not only served to students, teachers also have a very influential role in the progress of education in Indonesia and facing the 21st century marked by technological developments.